The Role of Parents in Developing Early Children's Social Skills - Lia Mustabyiah; Ali Formen; Sunawan Sunawan (Universitas Negeri Semarang, 2024)
Parents have an important role in providing education and care according to their functions and responsibilities for their children, including social skills. Social skills are children's skills in interacting with the surrounding environment. This study aims to find out about the role of parents in developing early childhood social skills in Ketro Hamlet. This research uses a qualitative type with ethnographic methods. The data collection process uses observation sheet instruments, interviews, and documentation. This study uses data validation techniques in the form of data collection triangulation and time triangulation. The data analysis used refers to the twelve stages in Spradley's theory. The results of the study show that the role of parents in Ketro Hamlet in developing early childhood social skills is carried out by habituation in everyday life that is adapted to the culture in Ketro Hamlet accompanied by social support from the community and adults around the child.